Food Safety Hazards and Microbiological Zoonoses in European Meat Imports Detected in Border Inspection in the Period 2008–2013. (29th May 2015) - Jansen, W.; Grabowski, N.; Gerulat, B.; Klein, G.
Summary: Microbiological contaminations and other food safety hazards are omnipresent within the European Union (EU) and a considerable risk for consumers, particularly in imported meat and meat products. The number of rejections at external EU borders has been increasing in recent years. Official authorities in each member state are therefore obliged to notify border rejections of food and animal feed due to a direct or indirect risk to human or animal health. This study explored the trends and temporal and spatial distribution of notifications on food safety hazards between January 2008 and December 2013 with a special emphasis on microbiological zoonoses in meat and meat products including poultry at border checks resulting from the rapid alert system for food and feed (RASFF). Results indicated that border rejection notifications are increasing exponentially, frequently due to Salmonella in poultry and shiga‐toxin‐producing E. coli in meat and meat products.